Conditioning on parental mating types can reduce necessary assumptions for Mendelian randomization - Ejima, Keisuke; Liu, Nianjun; Mestre, Luis Miguel; de los Campos, Gustavo; Allison, David B. (Frontiers in Genetics, 2023)
Mendelian randomization (MR) has become a common tool used in epidemiologic studies. However, when the confounding variables are correlated with the instrumental variable (in this case, a genetic/variant/marker), the estimation can remain biased even with MR. We propose conditioning on parental mating type (a function of parental genotypes) in MR to eliminate the need for one set of assumptions, thereby plausibly reducing such bias. We illustrate a situation in which the instrumental variable and the confounding variables are correlated by using two unlinked diallelic genetic loci: one an instrumental variable and the other a confounding variable. Assortative mating or population admixture can create an association between the two unlinked loci, which can violate one of the necessary assumptions for MR. We simulated datasets involving assortative mating and population admixture and analyzed them with three different methods: i) conventional MR, ii) MR conditioning on parental genotypes, and iii) MR conditioning on parental mating type. We demonstrated that conventional MR leads to type I error rate inflation and biased estimates for cases with assortative mating or population admixture. In the presence of non-additive effects, MR with adjustment for parental genotypes only partially reduced type I error rate inflation and bias. In contrast, conditioning on parental mating type in MR eliminated the type I error inflation and bias under these circumstances. Conditioning on parental mating type is a useful strategy to reduce the burden of assumptions and the potential bias in MR.